2020
DOI: 10.3390/nu12072008
|View full text |Cite
|
Sign up to set email alerts
|

Global Vitamin C Status and Prevalence of Deficiency: A Cause for Concern?

Abstract: Vitamin C is an essential nutrient that must be obtained through the diet in adequate amounts to prevent hypovitaminosis C, deficiency and its consequences—including the potentially fatal deficiency disease scurvy. Global vitamin C status and prevalence of deficiency has not previously been reported, despite vitamin C’s pleiotropic roles in both non-communicable and communicable disease. This review highlights the global literature on vitamin C status and the prevalence of hypovitaminosis C and deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
142
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 155 publications
(179 citation statements)
references
References 84 publications
(116 reference statements)
6
142
1
6
Order By: Relevance
“…Although other studies (in India and Brazil) have shown lower ascorbate concentrations in people with Parkinson’s disease compared to healthy controls [ 16 , 17 ], based on the low control values and the less than ideal analytical methodology used, it is possible that these low values were due to artifactual ex vivo oxidation [ 27 ]. Alternatively, individuals in low-middle income countries tend to have lower vitamin C status, and thus may be more prone to developing hypovitaminosis C during various disease states [ 32 , 33 ]. Of note, the Parkinson’s disease group in our study had a higher prevalence of hypovitaminosis C, where the subclinical symptoms of vitamin C deficiency start to become apparent [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although other studies (in India and Brazil) have shown lower ascorbate concentrations in people with Parkinson’s disease compared to healthy controls [ 16 , 17 ], based on the low control values and the less than ideal analytical methodology used, it is possible that these low values were due to artifactual ex vivo oxidation [ 27 ]. Alternatively, individuals in low-middle income countries tend to have lower vitamin C status, and thus may be more prone to developing hypovitaminosis C during various disease states [ 32 , 33 ]. Of note, the Parkinson’s disease group in our study had a higher prevalence of hypovitaminosis C, where the subclinical symptoms of vitamin C deficiency start to become apparent [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In high-income settings, females appear to have higher vitamin C status and a lower prevalence of deficiency than males [3]. According to McCall et al [28], UK males have a four-fold odds ratio of deficiency compared with females (Table 4).…”
Section: Sexmentioning
confidence: 99%
“…The difference in vitamin C status between males and females is thought to be partly a result of a volumetric dilution effect due to the higher fat-free mass of males [29]. There are also differences in dietary intakes between men and women, with women generally having comparable or higher intakes than men in high-income countries, although this difference is less apparent in some low-income settings [3]. It should also be noted that pregnancy and lactation typically lower women's vitamin C status due to hemodilution and the needs of the developing fetus and growing infant (see below).…”
Section: Sexmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary micronutrients intake was shown to be important for human health [10,11]. Particularly, vitamin C has pleiotropic effects on human health, possibly due to its antioxidant properties and cofactor functions for numerous biosynthetic enzymes [12]. In addition, vitamin C is widely considered to be important for optimal immunity [13].…”
Section: Of 11mentioning
confidence: 99%